Workshop Menu MP-ASI untuk Menjaga Status Gizi Balita di Kota Mataram - Baiq Fitria Rahmiati; Anthony Anggrawan; Nurul Hidayah; Junendri Ardian; M. Thontowi Jauhari; Wenny Wijaya (LPPM Universitas Bumigora, 2021)
Basic Health Research Data 2018 states that the prevalence of malnutrition in infants is 18.8%. MPASI, complimentary food to breast milk, is food or drink containing nutrients, given to babies or infants aged 6-24 months, and given in stages according to the age and digestive capacity of the babies or infants to meet their nutritional needs other than breast milk. This dedication aims to improve the nutritional status of infants under five years old by providing nutrition education to mothers of children under five related to the provision of complementary feeding recommended by WHO. The method used is counseling to 30 mothers of toddlers in Mataram City. The results of the community service activity show that there is an increase related to participants’ knowledge of complementary foods, solving problems for children who do not want to eat, and an increase in commitment to make complementary foods according to those recommended by WHO. The conclusion of this dedication is an increase in knowledge and willingness of mothers to provide food in accordance with WHO recommendations.